2018
DOI: 10.1007/s11738-018-2789-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a non-destructive method to estimate the leaf area of Armoracia rusticana

Abstract: The aim of the study was to analyze horseradish growth for developing a mathematical model to estimate the leaf area based on linear measurements of the leaf surface. Leaf area (LA), number, and morphometric characteristics of the leaves including lamina length (L) and width (W) were evaluated on two horseradish accessions (Cor and Mon) throughout a 2 year growing cycle. In both accessions, increased values of LA and leaf number were found by comparing the second with the first-growing season. Leaf development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Throughout the whole growing cycle of the first year (from leaf emergence by the end of April 2014 to root harvesting in January 2015), the maximum length of the lamina (L, from lamina tip to the point of petiole intersection along the midrib) and midlength width (W) of all the leaves of 4 plants for each accession were measured (to the nearest 0.1 cm with a simple ruler) every week. These parameters were subsequently fitted in the regression linear models LA = 0.71 LW -0.27 and LA = 0.76 LW -3.22 for COR and MON, respectively, to estimate the leaf area (LA), according to De Maria et al (2018). In addition, during both growing cycles (2014/15 and 2015/16), 4 plants for each accession were collected in three phenological stages: (S1) during the vegetative development of the plants (July), (S2) at the beginning of leaf senescence (September), and (S3) at root harvesting (January).…”
Section: Physiological Parameters and Plant Growth Analysis In Open Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the whole growing cycle of the first year (from leaf emergence by the end of April 2014 to root harvesting in January 2015), the maximum length of the lamina (L, from lamina tip to the point of petiole intersection along the midrib) and midlength width (W) of all the leaves of 4 plants for each accession were measured (to the nearest 0.1 cm with a simple ruler) every week. These parameters were subsequently fitted in the regression linear models LA = 0.71 LW -0.27 and LA = 0.76 LW -3.22 for COR and MON, respectively, to estimate the leaf area (LA), according to De Maria et al (2018). In addition, during both growing cycles (2014/15 and 2015/16), 4 plants for each accession were collected in three phenological stages: (S1) during the vegetative development of the plants (July), (S2) at the beginning of leaf senescence (September), and (S3) at root harvesting (January).…”
Section: Physiological Parameters and Plant Growth Analysis In Open Fieldmentioning
confidence: 99%
“…In both growing cycles analysed at stage S3 (root harvesting), the horseradish plants presented the old leaves completely dry and several new young leaves wrapped in a rosette, that weighed 14 and 42 g in January 2015 and 2016, respectively (average values between accessions) (Table 2). To our knowledge, no data is available in literature referring to plant growth and leaf area development other than those by De Maria et al (2018), who proposed non-destructive linear models to accurately estimate the leaf area of horseradish throughout the entire crop cycle. De Maria et al (2016) also stressed the importance of the leaves due to the richness of phytochemicals; indeed the authors reported that the rosette leaves contain a great GLS concentration up to ten-fold higher than roots during the harvesting period, and fivefold higher later, when the foliage is fully developed.…”
Section: Articlementioning
confidence: 99%
“…Automated equipment is urgently needed to replace manual grading. Nondestructive testing technology based on machine vision has become an inevitable trend of flower grading due to its good objective consistency and high efficiency [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%